2020
DOI: 10.3389/fphy.2020.00080
|View full text |Cite
|
Sign up to set email alerts
|

Anatomically Adaptive Coils for MRI—A 6-Channel Array for Knee Imaging at 1.5 Tesla

Abstract: Purpose: Many of today's MR coils are still somehow rigid and inflexible in their size and shape as they are intentionally designed to image a specific anatomical region and to fit a wide range of patients. Adaptive coils on the other hand, are intended to follow a one-size-fits-all approach, by fitting different shapes, and sizes. Such coils improve the SNR for a wide range of subjects by an optimal fit to the anatomical region of interest, and in addition allow an increased handling and patient comfort as on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Screen-printed MRI coils [17] developed by Corea et al have shown to be a reliable alternative to bulky conventional coils with comparable SNR, suitable especially for pediatric imaging [18]. Stretchable Rx coils produced with copper braids [19], [20], meandered conductors [21], liquid metal printed into neoprene support material [22], liquid metal filled tubes [23], [24] or conductive elastomers [25] mostly target wrist or knee imaging and offer a truly wearable solution.…”
Section: Introductionmentioning
confidence: 99%
“…Screen-printed MRI coils [17] developed by Corea et al have shown to be a reliable alternative to bulky conventional coils with comparable SNR, suitable especially for pediatric imaging [18]. Stretchable Rx coils produced with copper braids [19], [20], meandered conductors [21], liquid metal printed into neoprene support material [22], liquid metal filled tubes [23], [24] or conductive elastomers [25] mostly target wrist or knee imaging and offer a truly wearable solution.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we aim to improve both imaging sensitivity and acoustic transparency in one apparatus by presenting a very thin, low-profile, receive-only 8-channel head coil (FUS-Flex) operating at 3T. The design is inspired by stretchable [ 34 ], [ 35 ], flexible [ 36 ]–[ 40 ] and lightweight [ 41 ] coil technologies, offering a coil array with full conformity to the head. The novelty of our work lies in the use of very thin (~1 mm) RF elements (providing low interaction with the acoustic field), and the use of higher channel count than currently available in the literature, increasing the available imaging SNR, the sensitivity of the coil and improving/enabling parallel imaging.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lightweight, flexible coils are more comfortable 4 and can provide better SNR than rigid setups due to closer proximity to the imaging region. Examples include screen‐printing to create RF coils that are incorporated into infant blankets, 4 as well as flexible, meandering wires that allow the coil conductor’s path to change 5,6 . Conductive textiles can be stretched up to a 100 times their size, 7 and a flexible coil made from a conductive elastomer based on silver microparticles achieves an SNR just 14% lower than a reference copper coil 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Examples include screen-printing to create RF coils that are incorporated into infant blankets, 4 as well as flexible, meandering wires that allow the coil conductor's path to change. 5,6 Conductive textiles can be stretched up to a 100 times their size, 7 and a flexible coil made from a conductive elastomer based on silver microparticles achieves an SNR just 14% lower than a reference copper coil. 8 Liquid metal 9,10 and braided conductors 11 also allow for stretchable coils that closely fit moving and flexing body parts.…”
Section: Introductionmentioning
confidence: 99%